The use of a fiber sleeve to improve fracture strength of pulpless teeth with flared root canals. Issue 12 (December 2015) - Xiong, Yu; Huang, Shih-Hao; Shinno, Yuko; Furuya, Yu; Imazato, Satoshi; Fok, Alex; Hayashi, Mikako
Highlights: The FRP/sleeve combination effectively reinforced plupless premolars with flared root canals under firm bonding condition. The maximal principle stress in restored premolars increased dramatically, once interfacial de-bonding extended to their cervical region. Further firm bonding at the resin/dentin interface in an entire root should be achieved to reinforce pulpless premolars with flared root canals. Abstract: Objectives: This study aimed to investigate how use of a fiber sleeve may reduce interfacial debonding and improve fracture strength of pulpless teeth with flared root canals. Methods: Pulpless premolars with flared root canals were restored either with a fiber-reinforced post (FRP) alone or with an FRP wrapped in a hollow tubular fiber sleeve. A normal root restored with an FRP alone served as a control. The integrity of resin–dentin and resin–fiber interfaces in the restored roots was evaluated by a stereoscopic system after penetrating a dye. Four roots were tested for each experimental group. Fracture resistance in pulpless premolars with flared root canals restored with an FRP alone or with an FRP/sleeve combination were investigated under bonded and non-bonded conditions with static fracture testing ( n = 8), and stress distribution in these restored premolars were tested by finite element analysis (FEA). Results: Flared root canals restored with an FRP/sleeve combination demonstrated superior integrity at the cervical resin–dentin interface to root canals with an FRP alone. Premolars with a flared root canal restored with an FRP/sleeve combination showed significantly greater fracture resistance compared with premolars restored with an FRP alone. FEA showed that once interfacial de-bonding extended to the cervical region of the root, stress concentration in the root dentin dramatically increased. Significance: The FRP/sleeve combination was effective in reducing debonding and, hence, improving the fracture strength of pulpless premolars with flared root canals.